The musical story: another way of telling the story (Journal of Parents and Teachers, 2014)
Human beings use different languages, among which the literary, the musical and the corporal have especial importance. The link between music and literature occurs in songs, but also in stories. This article discusses some types of musical stories and the benefits they have for children.
Keywords: Literature; music; songs; poems; short stories; musical story; freedom; autonomy; personal development.